APPLICATION EXPERIENCE OF THE ENTERAL FEEDING IN A PATIENT WITH THE STENOSING FORM OF CROHN'S DISEASE - O.V. Ryazanova; A.S. Potapov; E.G. Tsimbalova; S.I. Polyakova; T.V. Strokova (Педиатрическая фармакология)
The article describes the rare form of crohn's disease acquired by a child with the localization in the pre pyloric stomach section and steno sing complications. Due to the development of the acute bowel obstruction, the girl underwent a surgery. taking into account her young age, hypotrophy, low activity of inflammation as well as the inability of the peroral administration of the anti inflammatory medications during the postoperative period, the girl was prescribed full enteral feeding with modulen IBD medical mixture for the patients suffering from the inflammatory intestinal diseases against which the doctors noted the positive clinical and laboratory dynamics.Key words: crohn's disease, enteral feeding, children.